The value of passenger rail access - Joschka Flintz (RWI - Leibniz-Institut für Wirtschaftsforschung, 2024)
This study quantifies the effect of train station openings on residential house prices across Germany over a 12-year period to provide generalizable evidence on the valuation of access to passenger rail by households. It is based on data on about 90 train station openings between 2009 and 2020 in Germany and a Differencein-Differences model that uses three different control group variants to cover alternative assumptions about unobserved regional heterogeneity to mitigate problems arising from endogenous transport infrastructure provision. The results indicate that train station openings increase residential house prices on average by 5% ( exteuro18,000) within a distance of up to two to three kilometers. Notably, these positive effects are observed exclusively for properties without prior access to passenger rail services, and are significantly larger in more densely populated and urban areas. – – Diese Studie quantifiziert die Auswirkungen von Bahnhofseröffnungen auf die Wohnimmobilienpreise in Deutschland über einen Zeitraum von 12 Jahren, um verallgemeinerbare Erkenntnisse über die Bewertung des Zugangs zum Schienenpersonenverkehr durch Haushalte zu gewinnen. Sie basiert auf Daten zu etwa 90 Bahnhofseröffnungen zwischen 2009 und 2020 in Deutschland und einem Differenz-in-Differenzen-Modell, das drei verschiedene Kontrollgruppenvarianten verwendet, um alternative Annahmen über unbeobachtete regionale Heterogenität abzudecken und Probleme, die sich aus der endogenen Bereitstellung von Verkehrsinfrastruktur ergeben, zu mildern. Die Ergebnisse zeigen, dass die Eröffnung von Bahnhöfen die Preise für Wohnimmobilien in einer Entfernung von bis zu zwei bis drei Kilometern im Durchschnitt um 5 % (18.000 exteuro) erhöht. Bemerkenswert ist, dass diese positiven Effekte ausschließlich für Immobilien ohne vorherigen Zugang zum Schienenpersonenverkehr beobachtet werden und in dichter besiedelten und städtischen Gebieten deutlich größer sind.
Keywords: C23; R21; R40; 330; Public transportation; regional passenger rail; hedonic price model; difference-in-differences; spatio-temporal analysis